2015
DOI: 10.1016/j.jclepro.2015.03.047
|View full text |Cite
|
Sign up to set email alerts
|

Removal of micropollutants by fungal laccases in model solution and municipal wastewater: evaluation of estrogenic activity and ecotoxicity

Abstract: a b s t r a c tThis study describes a multidisciplinary approach that investigates the breakdown potential of a laccase mediated system from Trametes pubescens MUT 2400 against several micropollutants including already recognized endocrine disrupting chemicals at their natural residual concentrations (from mg/L up to ng/ L).In model solution, the chemical speciation focused on a mixture of 18 analytes and adopted stir bar sorptive extraction with directed in-situ derivatization followed by gas chromatography a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 73 publications
(26 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…Most of the activity (54%) was lost after 24h-treatment of municipal wastewater (Spina et al 2015) and the same effect was observed by Tran and collaborators (2013) who reported that 30% of laccase activity was lost in only 4 hours.…”
Section: Laccases Vs Municipal Wastewaterssupporting
confidence: 76%
See 4 more Smart Citations
“…Most of the activity (54%) was lost after 24h-treatment of municipal wastewater (Spina et al 2015) and the same effect was observed by Tran and collaborators (2013) who reported that 30% of laccase activity was lost in only 4 hours.…”
Section: Laccases Vs Municipal Wastewaterssupporting
confidence: 76%
“…Oxybenzone removal required 2 hours (Garcia et al 2011), whereas 20,000 U/l completely removed estrogens in a wastewater sample within a 1 hours (Auriol et al 2008). The half-life was lower than 4 hours for 10 up to 18 micropollutants, and most of these occurred in the first minutes of the treatment (Spina et al 2015).…”
mentioning
confidence: 90%
See 3 more Smart Citations